ОРЧИН ҮЕИЙН УЛС ТӨРИЙН ШИНЖЛЭХ УХААНЫ ЧУХАЛ АСУУДАЛ: АРДЧИЛЛЫН ЧАНАР - Б.Эрдэнэдалай (Politology, 2023)
In this article has taken contemporary political science’s important issue is quality of democracy. Last years scientist are noted and researched this issue. Because democracy has spread and taken root in many parts of the world in the past three decades. A crucial element in mapping, explaining and encouraging this growth in democracy has been the need for valid, meaningful and reliable ways to measure and assess democratic progress and the quality of democracy itself.